Influence of feed ingredients and additives on mucosal health with focus on the intestine of Atlantic salmon (Salmo salar) - Sørensen, Solveig Lysfjord (Nord University, 2022)
Doctoral thesis (PhD) – Nord University, 2022 publishedVersion